Cabrio on the Verge - Darnall, John; Boyer, Don; Darnall, Jhon; Oldenbroek, Gary (Tennessee, USA Unison, 1995)
In the tradition of the vest contemporary jazz-pop artists, Cabrio creates original music which is melodic and rhythmic, intricate yet hummable. with its upbeat appeal, On the Vege sets the perfect mood for work or play, a dinner party or time alone
Content : Markee Markoo -- Best kept secret -- Lip Lock -- Don't Want to say Goodnight -- Dijon Bejing PM -- Underground -- Hypnotique -- Summer Love -- Hayse Blues
"ADD-analog recording, digital mixing, digital transfer"
sound recording
12
Keywords: Concerts; Harmony; Music; Orchestral music; Recreation; Rest; Symphony